The Messiah formerly known as Jesus : dispatches from the intersection of Christianity and pop culture - Breen, Tom (Baylor University Press, 2008)
Acclaimed "Internet Theologian" Tom Breen has written a satirical, tongue-in-cheek exploration of pop Christianity. Whether pondering why there are so many Christian rock bands but so few good Christian rock songs or providing helpful tips on writing hip translations of the Bible (hint: lose the boring parts and constantly mention celebrities), Breen offers whip-smart, non-stop fun, along with a side-splitting send-up of our contemporary obsessions